Determinant Analysis of Audit delay: Empirical Study on Companies in the Consumer cyclical Sector: Analisis Determinan Audit delay : Studi Empiris Pada Perusahaan Sektor Consumer cyclical - Murdijaningsih, Tjahjani; Bariyah, Sofwatul; Danuta, Krisnhoe Sukma (Procedia of Social Sciences and Humanities, 2022)
This study aims to analyze the effect of audit committees, independent commissioners, firm size, profitability and solvency on audit delay in cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) 2016-2020. The population in this study were 128 companies with a sampling technique using purposive sampling. This study used a sample of 30 companies. The research method uses multiple linear regression with panel data approach. The results showed that the audit committee and profitability had a significant negative effect on audit delay. The independent board of commissioners has a significant positive effect on audit delay. Firm size and solvency have no effect on audit delay. The implication of this research is that companies need to pay attention to factors that can affect the occurrence of audit delays such as audit committees, independent commissioners, firm size, profitability and solvency as considerations in avoiding audit delays.